2012
DOI: 10.1007/s10511-012-9223-z
|View full text |Cite
|
Sign up to set email alerts
|

Unusual recurrent eclipses of the UX Ori star WW Vul

Abstract: In a prolonged study (about 30 years) of the photometric activity of WW Vul we have discovered unusual eclipses in the light curve of this star. They last 2-3 years and repeat with a period of 13.9 years. One nontrivial feature of these eclipses is that in their deepest part the star's brightness increases. Changes in the color indices during these events indicate that the brightening of the star is caused by reduced extinction in the center of an extended gas-dust structure that periodically intersects the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Such asymmetries are often attributed to dust trapped in A&A 605, A122 (2017) large-scale vortices that are able to collect large amounts of dust grains with sizes of the order of ∼1 mm. Another indirect way to detect vortices in disks is the fortuitous observation of eclipses of a young star by the trapped dust in a highly inclined disk (Barge & Viton 2003;Rostopchina-Shakhovskaja et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such asymmetries are often attributed to dust trapped in A&A 605, A122 (2017) large-scale vortices that are able to collect large amounts of dust grains with sizes of the order of ∼1 mm. Another indirect way to detect vortices in disks is the fortuitous observation of eclipses of a young star by the trapped dust in a highly inclined disk (Barge & Viton 2003;Rostopchina-Shakhovskaja et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such asymmetries are often attributed to dust trapped in large-scale vortices which are able to collect large amounts of dust grains with sizes of the order of ∼ 1 mm. Another indirect way to detect vortices in disks is the fortuitous eclipses of a young star by the trapped dust in a highly inclined disk (Barge & Viton 2003;Rostopchina-Shakhovskaja et al 2012). In this paper, numerical simulations are performed to follow the evolution of dust particles embedded in a gas disk that contains a vortex.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) With a certain combination of the disc wind parameters and the radiation wavelength the polarization degree may not change or change in a narrow range during an eclipse. Rostopchina-Shakhovskaja et al (2012) observed such eclipses of the UX Ori star WW Vul.…”
Section: Introductionmentioning
confidence: 96%